Smallholder farmers' perception of climate change and adoption of climate smart agriculture practices in Masaba South Sub-county, Kisii, Kenya. Issue 4 (April 2021) - Nyang'au, Jared O.; Mohamed, Jema H.; Mango, Nelson; Makate, Clifton; Wangeci, Alex N.
Abstract: Many countries experience the negative impacts of climate change especially in the decline of agricultural productivity leading to decreased national and household food security. This study assessed smallholder farmers' perception of climate variability and change and their adaptation strategies in Masaba South Sub-County, Kisii County, Kenya. A multi-stage sampling technique was used to collect data from 196 smallholder farmers. Additionally, focused group discussions and key informant interviews were used. The study revealed that most farmers perceived climate changes. 88.3% of the respondents noted a decrease in rainfall, 79.1% reported poor rainfall distribution, 88.3% perceived a late onset of rainfall while 76.6% perceived an increase in temperature. The farmers' perception mirrored the actual climatic data trends for the area obtained from the meteorological department. The major climate-smart agriculture practices adopted by farmers in the area included; diversification of crops, change of planting time and crop rotation/mixed cropping. The adoption of climate-smart agriculture practices significantly correlated with the household size, monthly income, access to credit and farmers' perception of climate change. The study recommends the incorporation and prioritization of climate change in the county and government development agenda as a means of enhancing the uptake of climate-smart agricultural practices. Abstract : Climate-smart agriculture, climate variability and change, Perception, Adaptation